2015
DOI: 10.5194/os-11-439-2015
|View full text |Cite
|
Sign up to set email alerts
|

Water level oscillations in Monterey Bay and Harbor

Abstract: Abstract. Seiches are normal modes of water bodies responding to geophysical forcings with potential to significantly impact ecology and maritime operations. Analysis of high-frequency (1 Hz) water level data in Monterey, California, identifies harbor modes between 10 and 120 s that are attributed to specific geographic features. It is found that modal amplitude modulation arises from cross-modal interaction and that offshore wave energy is a primary driver of these modes. Synchronous coupling between modes is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The 2 min mode is a good example of where a distinct sinusoidal oscillation in period is found throughout the record. This behavior is also observed at Monterey (Park et al, 2015), Hilo, and Honolulu where high-resolution (1 Hz) data were available, but is not shown in Fig. 2.…”
Section: Continuous Modesmentioning
confidence: 73%
See 4 more Smart Citations
“…The 2 min mode is a good example of where a distinct sinusoidal oscillation in period is found throughout the record. This behavior is also observed at Monterey (Park et al, 2015), Hilo, and Honolulu where high-resolution (1 Hz) data were available, but is not shown in Fig. 2.…”
Section: Continuous Modesmentioning
confidence: 73%
“…Breaker et al (2008) noticed continuously present seiches in Monterey Bay, leading Breaker et al (2010) to consider several possible forcing mechanisms (edge waves, long-period surface waves, sea breeze, internal waves, microseisms, and small-scale turbulence) and to question whether or not "the excitation is global in nature". Subsequent analysis by Park et al (2015) confirmed continuous oscillations in Monterey Bay over a 17.8-year record, and presented kinematic analysis discounting potential forcings of internal waves and microseisms while suggesting that a persistent mesoscale gyre situated outside the bay would be consistent with a jet-like forcing. However, jet-like currents are not a common feature along coastlines and could not be considered a global excitation of continuous oscillations.…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations